The Correlation of Sympathetic Block Elevation and Body Mass Index with the Incidence of Hypotension in Sectio Caesarea Patients with Spinal Anesthesia - Indra, Indra pranata; Burhan, Asmat; Heri Wibowo, Tophan; Suandika, Made (Global Indonesia Health Care (GOICARE), 2025)
Background: Hypotension is a frequent complication seen in spinal anesthesia. During spinal anesthesia, hypotension is more common with increasing block height, and an elevated body mass index (BMI) is considered a risk factor. Purpose: The aims of this research were to study the incidence of hypotension associated with spinal anesthesia for cesarean section and to relate block height to BMI. Methods: This is a cross-sectional correlational analytic study. A purposive sampling technique was used in picking 42 participants. The main instrument used for data collection was observation sheets. Results: The Spearman rank test for bivariate data showed that 35.7% of participants with a BMI greater than 25 experienced hypotension. In addition, 64.3% of participants with mild block elevation also developed hypotension. The Spearman rank test indicated a correlation value of -0.483 with a p-value of 0.001, signifying a strong and negative statistically significant relationship between hypotension and elevation of sympathetic block. Conclusion: There exists a significant relation between BMI and incidence of hypotension, with correlation values of -0.461 and a p-value of 0.002, further asserting that both BMI and block height are important characteristics that can be utilized in predicting the hypotension following spinal anesthesia in cesarean section patients